Nokia Chennai plant : lessons from the turbulent journey and closure of the world's largest mobile manufacturing unit - Nath, Papri; Totawar, Abhishek; Chakraborty, Ayon; Nambudiri, Ranjeet (London : Neilson Journals Publishing, 2019)
On November 1, 2014 Nokia Chennai, the world's largest mobile manufacturing plant was shut down impacting more than 35,000 lives. Prakash headed the plant since its inception in April 2005 till the last mobile phone rolled out in November 2014. Collectively, labour strikes, tax issues, and the acquisition of the parent company, led to the shutdown of the Nokia's Chennai plant. The final year of operations turned out to be the most challenging for Prakash and his management team. Together they created possibilities which made the plant perform at its best - even during those final days. The case presents how collective effort helped in maintaining employee morale and translated into motivation for them to perform in times of crisis and uncertainty.
Originally Published In Nath, P., Totawar, A., Chakrabort, A., & Nambudiri, R. (2019). Nokia Chennai Plant: Lessons from the Turbulent Journey and Closure of the World's Largest Mobile Manufacturing Unit. Journal of Organizational Behavior Education, 12(1), 55-68. JOBE12-CS4.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Nokia (Firm) -- Case studies; Employee morale -- Case studies; Employee motivation -- Case studies